2011
DOI: 10.1063/1.3653242
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting terahertz metamaterials mimicking electromagnetically induced transparency

Abstract: We designed and fabricated planar terahertz (THz) metamaterials made from superconducting NbN films to mimic electromagnetically induced transparency (EIT) system. They are characterized using THz time domain spectroscopy over a temperature range from 8 to 300 K. High transmittance and large delay-bandwidth product at transparency window are demonstrated, which mainly arise from the enhanced coupling and decreased damping in superconducting state. The EIT-like spectral response could be tuned in a wide frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 24 publications
(34 reference statements)
1
62
0
Order By: Relevance
“…Superconducting metamaterials, resulting either from bare replacement of the metallic parts employed in conventional metamaterials by superconducting ones [37,12,11,38,39,40,41,42], or by constructing hybrid structures comprising superconducting components [43,44,45,46,47,48,14,49], or even by incoprorating the Josephson effect as in arrays of SQUIDs [50,18,19,32,24], have been already proposed and/or demonstrated experimentally. Their operation frequency spans a huge range, from zero [51,52,53,54] to microwaves [55,18,56,19,32] and to Terahertz [11,12,37,57,38,39,40,15,58,59,41,42] and visible [45] frequencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superconducting metamaterials, resulting either from bare replacement of the metallic parts employed in conventional metamaterials by superconducting ones [37,12,11,38,39,40,41,42], or by constructing hybrid structures comprising superconducting components [43,44,45,46,47,48,14,49], or even by incoprorating the Josephson effect as in arrays of SQUIDs [50,18,19,32,24], have been already proposed and/or demonstrated experimentally. Their operation frequency spans a huge range, from zero [51,52,53,54] to microwaves [55,18,56,19,32] and to Terahertz [11,12,37,57,38,39,40,15,58,59,41,42] and visible [45] frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Their operation frequency spans a huge range, from zero [51,52,53,54] to microwaves [55,18,56,19,32] and to Terahertz [11,12,37,57,38,39,40,15,58,59,41,42] and visible [45] frequencies. Moreover, researchers rely on particular superconducting devices to access the trully quantum metamaterial regime [30,60,61,62,63].…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [26][27][28][29], the authors realized active tuning of EIT-like effect through temperature control or changing the incident angle. However, we find that the frequency range of transparency window of EIT-like metamaterials can not be tuned when varying the incident angle.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Zhang et al demonstrated that a metamaterial molecule composed of a pair of "bright" and "dark" resonators can serve as a three-level "atom" with EIT-like properties, which was experimentally investigated by Giessen et al, soon [14][15][16]. Metallic fish-scals, U-shaped structure, ring resonators and some other structures were also employed to illustrate the EITlike slow light effect in metamaterials [17][18][19][20][21][22][23][24][25][26][27][28][29]. Especially, in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation